Can repetitive transcranial magnetic stimulation promote recovery of consciousness in patients with disorders of consciousness? A randomized controlled trial - Zhenyu Liu; Shanshan Wu; Shuwei Wang; Huijuan Wu; Hongliang Gao; Xiao Lu (NeuroImage: Clinical)
Background: Disorders of consciousness (DoC) are characterized by a broad decline in background excitatory synaptic activity and varying levels of cerebral network disruption. Repetitive transcranial magnetic stimulation (rTMS), a neuromodulatory technique, is anticipated to assist the recovery of consciousness. Nonetheless, ongoing debates persist regarding its effectiveness, in light of the inconsistent results of recent research. Objective: The purpose of this study is to investigate the efficacy of rTMS in promoting recovery of consciousness in patients with DoC and to probe its impact on activity of cerebral functional networks. Methods: Forty-eight patients with DoC were included in this randomized controlled trial (Chinese Clinical Trial Registry: ChiCTR2100044930). Twenty-four patients in the control group accepted conventional therapy. Another 24 patients in the rTMS group received extra rTMS over the dorsolateral prefrontal cortex (DLPFC) once per workday during a 4-week intervention phase. Primary outcome was the proportion of patients emerging improvement on level of consciousness (LOC) based on coma recovery scale- revised (CRS-R) at the end of intervention. Furthermore, other behavioral scales such as the clinical global impression-improvement (CGI-I) and resting state-electroencephalography (rs-EEG) microstate were employed as secondary outcomes. Different microstates served as tools to detect the activity of respective corresponding resting state cerebral functional networks. Results: In comparison to the control group, the rTMS group exhibited a higher proportion of patients emerging improvement on LOC at post-intervention, with a risk ratio of 3.06 (95 % CI 1.54 to 6.09, P = 0.001). The distribution of patients with each grade of CGI-I across the groups also implied a trend that favored the rTMS group (common odds ratio:0.20, 95 % CI 0.065 to 0.63, P = 0.006). With respect to microstate E, the rTMS group had a significantly reduced global explained variance (GEV) was observed in the rTMS group (Z = -2.61, Pbonf = 0.027). Conclusion: High-frequency rTMS over the DLPFC could promote recovery of consciousness in patients with DoC. It might get involved in modulating the balance among cerebral functional networks and facilitating consciousness recovery.